Validação de instrumento para punção venosa periférica com cateter agulhado - Oliveira, Aminna Kelly Almeida de (2015)
Objective: to validate an instrument for the assessment of the peripheral venipuncture technique with over-the-needle catheter. Methods: methodological, transversal study developed with 24 judge nurses, professors of the subject semiology and/or physical examination techniques, with at least 1 year of experience in those disciplines in three stages: preparation of checklist; submission to the judges for evaluation; and content validation through the application of the Kappa index. Results: out of the 26 items of the instrument, only 2 did not have Kappa index and content validity index within the established parameters. Out of these 24 items, 7 showed perfect concordance index, 10 great and 7 good. Conclusion: the instrument had representation and extension about the area of interest.